Optimal damages multipliers in oligopolistic markets - Florian Baumann; Tim Friehe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper establishes that tort damages multipliers higher than one can be an instrument to induce imperfectly competitive producers to invest in product safety at socially optimal levels. In their selection of product safety levels, producers seek to maximize profits, neglecting the fact that higher investment in product safety increases consumer welfare; the discrepancy between private and social safety incentives can be remedied by setting damages multipliers to values greater than one. We show that the optimal damages multiplier depends on the characteristics of competition, such as the number of firms, the degree of substitutability/complementarity when products are heterogeneous, firms' cost structures, and the mode of competition.
Keywords: K13; H23; 330; product liability; product safety; market power; level of damages; punitive damages